(untitled) (Communications in Computational Physics, 2018)
In this paper, we will develop a first order and a second order convex splitting, and a first order linear energy stable fully discrete local discontinuous Galerkin (LDG) methods for the modified phase field crystal (MPFC) equation. In which, the first order linear scheme is based on the invariant energy quadratization approach. The MPFC equation is a damped wave equation, and to preserve an energy stability, it is necessary to introduce a pseudo energy, which all increase the difficulty of constructing numerical methods comparing with the phase field crystal (PFC) equation. Due to the severe time step restriction of explicit time marching methods, we introduce the first order and second order semi-implicit schemes, which are proved to be unconditionally energy stable. In order to improve the temporal accuracy, the semi-implicit spectral deferred correction (SDC) method combining with the first order convex splitting scheme is employed. Numerical simulations of the MPFC equation always need long time to reach steady state, and then adaptive time-stepping method is necessary and of paramount importance. The schemes at the implicit time level are linear or nonlinear and we solve them by multigrid solver. Numerical experiments of the accuracy and long time simulations are presented demonstrating the capability and efficiency of the proposed methods, and the effectiveness of the adaptive time-stepping strategy.